Short eternity or The long end of Soviet academicism - Володимир Верлока (Філософія освіти)
This article is the Opus postum of the author, who passed away in September 2023. Volodymyr Verloka is the author of numerous translations of philosophical classics from English, worked in various academic institutions, including the Institute of Philosophy of the National Academy of Sciences of Ukraine and the V. I. Vernadskyi National Library of Ukraine. He received his philosophical education at the beginning of the 1990s and personally witnessed the Soviet period of Ukrainian philosophy. The author’s critical reflections offered here are largely the result of his own experience of participating in the work of various academic institutions of independent Ukraine, and are also an honest expression of his sincere desire to change the situation with Ukrainian science and higher education for the better. In the article, the author addresses the reconstruction of the specific understanding of science in the USSR, revealing such features as ideological, partisan, and bureaucratic. The author analyzes the documents of the era – the publication of texts by Friedrich Engels, Vladimir Lenin, Volodymyr Vernadskyi, Nikolay Bukharin, Petr Kapitsa regarding the role of science in society. The author also turns to the analysis of the key philosophical texts of the era, which are direct evidence of the open position of Soviet philosophers on various issues, such as the definition of science, truth, and practice, and also finds out the specific influence of the doctrine of communism on the idea of Soviet academicism as the only politically permissible and at the same time as supposedly the only scientifically possible academic position. For this purpose, the author primarily analyzes the texts of the Soviet “Philosophical Encyclopedia”. The author also refers to critical sources that analyze the Soviet era – the works of Alain Besançon, Nelli Motroshilova, Anatolii Yermolenko and Serhii Yosypenko, Evert van der Zweerde and others. The author also gives his own critical assessment of the presence of vestiges of Soviet academicism in the modern Ukrainian academic sphere.